Corrosion characteristics of 316L as transpiring wall material in supercritical water oxidation of sewage sludge. (3rd August 2017) - Xu, Donghai; Ma, Zhijiang; Guo, Shuwei; Tang, Xingying; Guo, Yang; Wang, Shuzhong
Abstract: Systematical corrosion tests of austenitic stainless steel 316L exposed to sewage sludge SCWO (supercritical water oxidation) were conducted in a batch stirred reactor with hydrogen peroxide as oxidant. Experiment conditions such as temperature, oxidation coefficient, pH value, corrosion medium, were chosen mainly keeping in mind the place and environment of reactions (i.e. surrounding transpiring wall). The exposed samples were ultimately analyzed by weight measurement, scanning electron microscopy in conjunction with energy dispersive spectroscopy, and X-ray diffraction analysis. The results show that severe pitting corrosion occurred as the sample was exposed to complicated environments, and different oxides including Fe3 O4, FeCr2 O4 and MoO3 were found on the sample surface. The corrosion rate at all test conditions (360–450 °C pH = 5.2–10.05, oxidation coefficient of 0–2.0, sewage sludge or its SCWO reactor effluent) was in the range of 0.12–0.66 mm/y, and it increased as temperature and OC increased at supercritical conditions. Moreover, potential corrosion mechanism of 316L in sewage sludge SCWO is proposed, and influences of operating parameters on 316L corrosion properties are summarized. 316L and reactor effluent could be considered as transpiring wall material and transpiring water in sewage sludge SCWO with transpiring wall reactor, respectively. Highlights: Corrosion behavior of 316L in SCWO of sewage sludge and its effluent were studied. Influences of typical operation parameters on corrosion of 316L were explored. Potential corrosion mechanism on 316L in sewage sludge SCWO was proposed. The feasibility of 316L as transpiring wall material in SCWO was evaluated.